Sensitivity Enhancement for Fiber Bragg Grating Strain Sensing Based on Optoelectronic Oscillator With Vernier Effect - Xiaozhong Tian (IEEE, 2021)
Based on a dual-loop optoelectronic oscillator (OEO) with Vernier effect, a scheme of fiber Bragg grating (FBG) interrogation system with an improved scale factor has been proposed and experimentally demonstrated. Functioning as the optical carrier of the OEO, the reflection signal of two cascaded FBGs is divided into two optical beams by using a wavelength division multiplexer (WDM). The two optical beams at different wavelengths travel along single mode fibers with different lengths. After combined together by another WDM, the two optical beams go through a section of dispersion compensation fiber (DCF). The oscillating frequency shift of the OEO is determined by the overall time delay, which is affected by the wavelength change of the sensing FBG. Thus, the wavelength change of the sensing FBG can be converted into the oscillating frequency shift of the OEO. Furthermore, due to the length difference between the two optical beams, an obvious Vernier effect has been generated in the frequency response of the OEO. By detecting the frequency shift of the envelope peak of the frequency response curve, the sensitivity of the sensing interrogation can be enhanced greatly. A proof-of-concept OEO-based FBG sensor for axial strain sensing experiment is performed. The experimental results show that the sensitivity is about 0.31 KHz/μϵ for a single-loop OEO. By employing Vernier effect, the sensitivity can be improved to -11 KHz/μϵ, which is 35 times higher than that of the single-loop OEO.